1999
DOI: 10.1021/jo990428k
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-Step Diastereo- and Enantioselective Formation of trans-Azetidinones and Its Application to the Total Synthesis of Cholesterol Absorption Inhibitors

Abstract: An efficient and practical asymmetric process was developed for the synthesis of azetidinone-based cholesterol absorption inhibitors. Key to this synthesis was the discovery of a novel one-step diastereo- and enantioselective formation of trans beta-lactams starting from commercially available 3(S)-hydroxy-gamma-lactone. Various trans beta-lactams can be prepared in good yields and with better than 95:5 enantio- and diastereoselctivity. A Lewis acid-catalyzed aldol condensation and a highly enantioselective ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Buflomedil (170) has like bencyclane besides the vasodilator also antispasmodic properties. It is made by alkylation of pyrrolidine with 4-chlorobutyronitrile, followed by a Friedel-Crafts acylation of 1,3,5-trimethoxybenzene [384].…”
Section: Other Vasodilatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Buflomedil (170) has like bencyclane besides the vasodilator also antispasmodic properties. It is made by alkylation of pyrrolidine with 4-chlorobutyronitrile, followed by a Friedel-Crafts acylation of 1,3,5-trimethoxybenzene [384].…”
Section: Other Vasodilatorsmentioning
confidence: 99%
“…This chiral reduction yielded the desired alcohol in a diastereoselectivity of 93-95 %[175]. Further methods for preparation of ezetimibe are described and patented in[169][170][171][172][173][174].…”
mentioning
confidence: 99%
“…66) The relationship of the esters 4i and 5i with the b-lactams 10i and 11i was confirmed by chemical correlation: the amino esters 4i and 5i were cyclized, respectively, into 10i and 11i upon treatment with lithium hexamethyldisilazide. [12][13][14][30][31][32][33][34][35][36] Although the detailed reaction mechanism is not clear, it is likely that some facts obtained are consistent with the stereochemical outcome which involves a Zimmerman-Traxler transition state model 67,68) (Fig. 3).…”
mentioning
confidence: 93%
“…12-14) Chiral versions of these condensations have also been devised by the use of imines with a chiral auxiliary, [1][2][3][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] chiral ester enolate derivatives, [30][31][32][33][34][35][36] and chiral Lewis acids. [37][38][39][40][41] In the course of our studies on remote asymmetric induction using chiral sulfoxides, we previously reported the lanthanoid triflate-catalyzed Mukaiyama aldol reaction of sulfinyl aldehyde 1 with silyl ketene acetals.…”
mentioning
confidence: 99%
See 1 more Smart Citation